Calibrating H2S strip test against multiple tube fermentation technique using turbidity at incubation temperatures of 8 C, 18 C and 25 C - Tallod, Rolly A. (2012)
The assessment of H2S strip test for detection and measurement of fecal coliform in surface water at 8°C, 18°C and 25°C incubation temperature was evaluated by analyzing a total of 270 samples from the creek crossing the Beta-Epsilon Way in the University of the Philippines Diliman Campus. Parallel test was conducted using the Multiple Tube Fermentation Technique (MTFT) to determine the Most Probable Number (MPN) of the coliform in the sample. The study show that H2S strip test can detect fecal contamination at incubation temperature of 18°C to 25°C with 100% agreement with the MTFT method provided that it will be incubated for 23 hours and 34 hours respectively. H2S strip test demonstrates a low agreement 63% with MTFT at 8°C incubation temperature compared to 100% for both 18°C and 25°C. Coliform density was correlated to optimum reaction time and change in turbidity using a best fit curve. Maximum correlation of 96.30% and 96.6% at 25°C were obtained respectively. The data also show that quantitative and qualitative measurement of water sample at an incubation temperature of 25°C can be done within a 4 hour period using the H2S strip test. Thus, the H2S strip test can be used as primary method in the detection and measurement of fecal coliform in surface waters for providing result.
Thesis (M.S. Environmental Engineering)--University of the Philippines, Diliman
Keywords: Water -- Pollution